Inorganic Micelles (Hydrophilic Core@Amphiprotic Shell) for Multiple Applications. (1st September 2015) - Islam, Md. Shahinul; Choi, Won San; Kim, Sun Ha; Han, Oc Hee; Lee, Ha‐Jin
Abstract : A facile approach for synthesizing superhydrophobic hollow silica micelles (SHSMs) with hydrophilic cores and amphiprotic (superhydrophobic/hydrophilic) shell structures that act as "all‐in‐one" smart nanomaterials is presented. The particles possess hydrophilic cores consisting of silica and a polyelectrolyte (PE) network and an amphiprotic shell consisting of superhydrophobic long‐chained hydrocarbons and hydrophilic PEs. Due to the unique hydrophilic cores and amphiprotic shells, the particles exhibit extraordinary performance in terms of amphiprotic catalytic reactions in organic and aqueous solutions, oil/water separation and pollutant purification, and an ultrahigh loading capacity of enzymes with significant stability and efficient recyclability. The amphiprotic functionalities of the SHSMs have the potential to allow for a rich range of applications to be explored. Abstract : Superhydrophobic hollow SiO2 micelles (SHSMs) with hydrophilic cores and amphiprotic (superhydrophobic/hydrophilic) shells are prepared and their multiple applications are demonstrated. The unique amphiprotic functionality makes the SHSMs suitable as smart nanomaterials for multiple applications, such as amphiprotic catalytic reactions in aqueous or organic solutions, oil/water separation and pollutant purification, and enzyme immobilization, with great stability and efficient recyclability.